2017
DOI: 10.3847/1538-4357/835/1/110
|View full text |Cite
|
Sign up to set email alerts
|

HERSCHEL EXTREME LENSING LINE OBSERVATIONS: [C ii] VARIATIONS IN GALAXIES AT REDSHIFTS z = 1–3*

Abstract: We observed the [C II] line in 15 lensed galaxies at redshifts 1<z<3 using HIFI on the Herschel Space Observatory and detected 14/15 galaxies at 3σ or better. High magnifications enable even modestly luminous galaxies to be detected in [C II] with Herschel. The [C II] luminosity in this sample ranges from 8 × 107 L e to 3.7 × 10 9 L e (after correcting for magnification), confirming that [C II] is a strong tracer of the ISM at high redshifts. The ratio of the [C II] line to the total far-infrared (FIR) lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…This is especially true when considering the high-z galaxies with especially pronounced deficit behaviour. For example, the z ∼ 2-6 galaxies observed in Rawle et al (2014), Capak et al (2015), De Breuck et al (2014), Gallerani et al (2012), andMalhotra et al (2017) show [C II]/TIR ratios 10 to 100 times lower than those observed in the local star-forming galaxies included in this work. As the majority of [C II] emission has been found to arise from the neutral phases of the ISM (Pineda et al 2013;Abdullah et al 2017;Croxall et al 2017;Cormier et al 2019;Sutter et al 2019;Bigiel et al 2020), the effects of thermalization solely within the ionized phases of the ISM can only contribute to moderate deficit behaviour.…”
Section: Discussion a N D C O N C L U S I O Nmentioning
confidence: 52%
“…This is especially true when considering the high-z galaxies with especially pronounced deficit behaviour. For example, the z ∼ 2-6 galaxies observed in Rawle et al (2014), Capak et al (2015), De Breuck et al (2014), Gallerani et al (2012), andMalhotra et al (2017) show [C II]/TIR ratios 10 to 100 times lower than those observed in the local star-forming galaxies included in this work. As the majority of [C II] emission has been found to arise from the neutral phases of the ISM (Pineda et al 2013;Abdullah et al 2017;Croxall et al 2017;Cormier et al 2019;Sutter et al 2019;Bigiel et al 2020), the effects of thermalization solely within the ionized phases of the ISM can only contribute to moderate deficit behaviour.…”
Section: Discussion a N D C O N C L U S I O Nmentioning
confidence: 52%
“…A decade later, the Infrared Space Observatory (ISO; Kessler et al 1996) increased the number of galaxies with FIR fine-structure line detections to the dozens (Malhotra et al 1997Luhman et al 1998Luhman et al , 2003. But twenty more years needed to pass until the Herschel Space Observatory (Herschel hereafter; Pilbratt et al 2010) reopened a new window into the FIR universe, providing spectroscopic data for significantly larger samples of nearby, intermediate-redshift, and high-redshift galaxies (e.g., Graciá-Carpio et al 2011;Díaz-Santos et al 2013Magdis et al 2014;Rigopoulou et al 2014;Brisbin et al 2015;Cormier et al 2015;Rosenberg et al 2015;Malhotra et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the case that the [C ii]/FIR ratio is significantly low, the expected [C ii] flux is fainter than the detection limit of our ALMA observations. Although such a lower [C ii]/FIR value suggests higher dust temperature (Malhotra et al 2017), optical observations imply that DLA2233+131 may have only little dust content. This is consistent with the non-detection of dust continuum from DLA2233+131 in this work.…”
Section: Discussionmentioning
confidence: 99%